Atomic Scale Catalysts: Atomic Scale Materials for Emerging Robust Catalysis (Small Methods 11/2018). Issue 11 (5th November 2018) - Sun, Xian; Chen, Yunxu; Liu, Keli; Ding, Yu; Zeng, Mengqi; Fu, Lei
Abstract : In article1800181, Mengqi Zeng, Lei Fu, and co‐workers review a class of high‐efficiency atomic scale materials (ASMs) catalysts. The distinct structural characteristics endow them with great catalytic advantages, especially the maximum atomic utilization. ASMs catalysts have demonstrated their superior catalytic performance in various core catalytic reaction systems. It is envisioned that these will open up a new territory in catalysis.